STUDY OF THE PLYWOOD PANELS PROPERTIES USING GEOSTATISTIC - Pinheiro, Cleverson [UNESP]; Campos, Cristiane Inacio de [UNESP]; Oliveira de Matos, Carlos Alberto [UNESP]; Sampaio Alves, Manoel Cleber de [UNESP]; Valarelli, Ivaldo De Domenico [UNESP]; Ribeiro, Marcos Valerio [UNESP]; Amaral, Simone Simoes [UNESP] (Inst Federal Educacao, Ciencia & Tecnologia Sao Paulo, 2016)
Plywood panels have multiple applications in construction, in the furniture industry and packaging. There is a need to improve techniques for assessing quality of these products. This paper proposed the use of geostatistics to evaluate the behavior of the of the plywood panel. The physical properties were analyzed (moisture content, density and water absorption) in the full extent of the plywood panel of Eucalyptus sp., bonded with adhesive single-component polyurethane. For analysis, three panels of five layers, with dimensions of 350 x 350 x 15.5 mm each, were employed. The tests were based on the standards EN 323-2000, EN 322-2000 and ABNT NBR 9486- 2011. Statistical modeling was performed using the R software, using the methodology of geostatistics. The average results were compared with values reported in the literature. The average water absorption was 7% higher in comparison with other studies, which used urea formaldehyde. So, the product can be applied only to interior and their use is not advisable for floors; the average moisture content and density were within the average values found in the literature. The behavior of the properties analyzed using the geostatistical model was not homogeneous, with large variations. Geostatistics was considered an appropriate tool for the study of the variability of the plywood panel properties, and can be applied for better quality control of them.
Keywords: plywood; moisture content; density; water absorption; geostatistics